2004
DOI: 10.1080/10236210490506425
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Interaction Between a Transonic Turbine Stage and Downstream Components

Abstract: Results from a numerical simulation of the unsteady flow through one quarter of the circumference of a transonic high-pressure turbine stage, transition duct, and low-pressure turbine first vane are presented and compared with experimental data. Analysis of the unsteady pressure field resulting from the simulation shows the effects of not only the rotor/stator interaction of the high-pressure turbine stage but also new details of the interaction between the blade and the downstream transition duct and low-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Total-to-static efficiency curves depicted in figure 5 show that 1D model has acceptable accuracy till u/C0=0.4 and then the discrepancy sees a constant increase. This is likely to be due to additional losses from interaction of transonic discharge flow with a downstream hood which are only captured via transient simulations as described by Davis (2004).…”
Section: Numerical Simulation Methodology Validationmentioning
confidence: 99%
“…Total-to-static efficiency curves depicted in figure 5 show that 1D model has acceptable accuracy till u/C0=0.4 and then the discrepancy sees a constant increase. This is likely to be due to additional losses from interaction of transonic discharge flow with a downstream hood which are only captured via transient simulations as described by Davis (2004).…”
Section: Numerical Simulation Methodology Validationmentioning
confidence: 99%
“…In addition to efficiency improvement, clocking can also influence the time-resolved characteristics of a turbomachinery system, resulting in a reduction of noise and vibrations. Davis et al [9] investigated a transonic HPT with a downstream transition duct and LPT vanes and addressed the interaction among the rotor blade, the intermediate turbine duct, and the second vane. Gadea et al [10] studied the influence of clocking on the time-resolved pressure field of a second vane tested in a 1.5-stage HP turbine without a transition duct.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical calculations provided velocity distributions and profile losses for three vane configurations with one, two and three smaller aero-vanes. Davis et al [24] reported an experimental and numerical research for a LP vane in a s-shaped duct preceded by a transonic HP stage. The author concludes that interactions between the rotor and second vane increase the unsteadiness in both rows but this slightly affects the overall aerodynamic losses.…”
Section: Introductionmentioning
confidence: 99%